PERFORMANCE IS INFLUENCED BY JOB INSECURITY AND OCCUPATIONAL SAFETY HEALTH - Dirga Lestari; Siti Maria (AFEBI Management and Business Review, 2018)
The purpose of this study was to investigate the influence between Job Insecurity and Occupational Safety and Health (OSH). It was expected that Job Insecurity was positively related to Job Performance and to Occupational Safety and Health (OSH). Some Firefighter And Rescue Department in East Kutai Regency sampled in this study and the result of the proposed hypothesis is acceptable. Job insecurity was in fact positively correlated with Job Performance and positively with Occupational Safety and Health (OSH). However, results of this research indicate to improve the performance required not only the safety and personal health of employees physically but also the work security from the psychological side of within the workers themselves. This applies not only to firefighters but also to other sector workers. Limitations of the study are the use of a sample of only one hundred and twenty-six firefighter and a need for more in-depth interviews to more Firefighter And Rescue Department in East Kutai Regency.Keywords: Job Insecurity, Occupational Safety and Health, Performance